QR CODE IN GRAMMY87 GAME AS NEW TECHNIQUES FOR MASTERING GRAMMAR - Dilia, Dilia Dewi; Hermawan, Dadang; Putri, Dian Rahmani (Yavana Bhasha : Journal of English Language Education, 2024)
The Challenges in Traditional Grammar Teaching grammar often rely on rote memorization and repetitive exercises, which can lead to student disengagement and boredom. Without context or interactive elements, students may find it hard to retain grammar rules and apply them correctly in their writing and speaking. Research in educational psychology emphasizes the benefits of active learning, where students participate actively in the learning process, rather than passively receiving information. Incorporating game elements in education can increase motivation, engagement, and retention. Games provide a dynamic and enjoyable way to learn complex concepts like grammar. The primary goal of Grammy87 is to be creative learning tools to improve students' grammar skills through a board game that is both educational and entertaining. The game aims to transform the learning experience from a mundane task into an exciting adventure by the use of technology of QR code scanning barcode to make easier for everybody to play without the assistance of a teacher. Techniques for gathering data that involve both direct observation and interviews. Data are analyzed using a descriptive qualitative approach, and they are then presented in a narrative format. The R&D procedures were modified from Borg and Gall's (1983) ten-cycle method of creating The Grammy87 Card game. Leveraging the principles of game design and educational research, Grammy87 significantly enhance grammar skills in a fun and motivating way. Integrating technology, providing clear learning paths, and ensuring the game is adaptable to various learning environments are key factors in its success.